A novel and potent dihydroorotate dehydrogenase inhibitor suppresses the proliferation of colorectal cancer by inducing mitochondrial dysfunction and DNA damage. Issue 1 (19th July 2022) - Yang, Xiaowei; Li, Chungen; Gou, Kun; Liu, Xiaocong; Zhou, Yue; Zou, Jiao; Chen, Qiang; Luo, Youfu; Zhao, Yinglan
Abstract: Dihydroorotate dehydrogenase (DHODH) is a quite attractive target in cancer therapy. Nevertheless, the antitumor effects of DHODH inhibitors against colorectal cancer (CRC) and the underlying mechanism have seldom been studied. Here, we explored the anti‐CRC efficacy of M62, a novel and potent DHODH inhibitor. In the study, M62 significantly inhibited the proliferation of CRC cells and induced S phase arrest. The antiproliferative effects caused by M62 were rescued by uridine supplementation. Mechanistically, messenger RNA sequencing results showed that M62‐triggered gene changes related to mitochondrial dysfunction, DNA damage, and DNA damage repair. Further validation showed that M62 treatment induced the generation of reactive oxygen species and decreased ΔΨm and ATP production. Meanwhile, M62 induced the accumulation of γ‐H2AX and longer comet tail moment, which were both markers of DNA damage. The downregulated DNA repair proteins and PI3K/ATK pathway were observed after M62 treatment. Furthermore, M62 significantly inhibited CRC xenograft tumor growth without detectable toxicity. Therefore, we conclude that M62 inhibits CRC growth both in vitro and in vivo by causing mitochondrial dysfunction and DNA damage, suggesting that DHODH inhibitors are potential therapeutic strategies for treating CRC. Abstract : Schematic diagram depicting the underlying mechanism by which M62 inhibits human colorectal cancer (CRC) cell growth. Dihydroorotate dehydrogenase inhibitor M62 induces mitochondrial dysfunction by upregulating the production of reactive oxygen species and consequent DNA damage, which, in turn, inhibits the growth of CRC cells. Moreover, the inhibition of PI3K/AKT pathway followed by DNA damage repair suppression also contributes to the anti‐CRC effect of M62.